Learning to Pray Better: Exploration of Jesus’ Prayer Life and His Our Father - Hidayat, Elvin Atmaja (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2021)
In the midst of the busy world and various other problems in life such as the pandemic that seems endless, people tend to feel bored, afraid, and depressed. Prayer as a means of communication with God is one of the simple ways in which the believers can find help and comfort. Prayer becomes a spiritual activity that has the potential to raise the mood, to contribute a sense of peace, optimism, and courage. However, even among the Christians not everyone knows how to pray. One might need a spiritual director, one of whose duties is to guide the faithful in prayer. One can be a guide in prayer if he or she is experienced and really passionate about faith. The most important model in the Christian prayer life is Jesus himself. According to the Gospels, his life is filled with prayer activities at all times and in various places, and his life can be seen as a ‘prayer’ as it is always directed to God, his Father. Jesus gives a beautiful prayer that becomes a model of all prayers, namely the “Our Father”. This article spiritually explores how Jesus teaches his disciples to pray from a practical point of view. With his “Our Father” Jesus teaches how to pray properly and correctly from particular aspects, one of which is to whom one should pray and what things one should ask for in prayer. By way of this exploration, one can learn that Jesus is “a master of prayer” to learn from to pray better.